Sphingolipid metabolism-related genes for the diagnosis of metabolic syndrome by integrated bioinformatics analysis and Mendelian randomization identification - Weidong Li; Qixing Zhong; Naisheng Deng; Xinhao Zhou; Haitao Wang; Jun Ouyang; Zhifen Guan; Bohao Cheng; Lijun Xiang; Yueming Huang; Yao Wang (Diabetology & Metabolic Syndrome)
Abstract Background The rising global incidence of metabolic syndrome (MetS) highlights the need for more effective diagnostic and therapeutic tools. Sphingolipid metabolites are crucial in MetS pathogenesis, and identifying related biomarkers could improve treatment strategies. Methods Differentially expressed genes (DEGs) were extracted from the GSE181646 dataset and compared with sphingolipid metabolism-related genes (SMRGs) to identify differentially expressed SMRGs (DE-SMRGs). Key module genes were obtained via Weighted Gene Co-expression Network Analysis (WGCNA). Machine learning and receiver operating characteristic (ROC) curve validation were used to screen biomarkers, followed by Gene Set Enrichment Analysis (GSEA) and immune cell infiltration analysis. Mendelian randomization (MR) was conducted to explore causal relationships between biomarkers and MetS-related diseases. Results A total of 701 DEGs, 599 key module genes, and 30 candidate genes were identified. PTPN18 and TAX1BP3 were validated as biomarkers and were found to be enriched in neuroactive ligand-receptor interactions and vascular smooth muscle contraction pathways. The levels of five immune cell types, including plasmacytoid dendritic cells, exhibited notable differences between the MetS and normal samples. TAX1BP3 exhibited a markedly negative correlation with activated CD8 T cell (r = -0.584), whereas it showed a markedly positive correlation with plasmacytoid dendritic cells (r = 0.744). MR analysis revealed that PTPN18 acted as a protective factor against obesity (P < 0.05, OR = 0.702), hyperlipidemia (P = 0.0015, OR = 0.855), and type 2 diabetes (P = 0.0026, OR = 0.953), but was associated with elevated fasting blood insulin (P < 0.05, OR = 1.036). Conclusion PTPN18 and TAX1BP3 were identified as sphingolipid metabolism-related biomarkers for MetS, offering potential promising targets for therapeutic intervention.